Patient safety culture in care homes for older people: a scoping review - Gartshore, Emily; Waring, Justin; Timmons, Stephen (BioMed Central, 2017)
Background: In recent years, there has been an increasing focus on the role of safety culture in preventing incidents such as medication errors and falls. However, research and developments in safety culture has predominantly taken place in hospital settings, with relatively less attention given to establishing a safety culture in care homes. Despite safety culture being accepted as an important quality indicator across all health and social care settings, the understanding of culture within social care settings remains far less developed than within hospitals. It is therefore important that the existing evidence base is gathered and reviewed in order to understand safety culture in care homes. Methods: A scoping review was undertaken to describe the availability of evidence related to care homes’ patient safety culture, what these studies focused on, and identify any knowledge gaps within the existing literature. Included papers were each reviewed by two authors for eligibility and to draw out information relevant to the scoping review. Results: Twenty-four empirical papers and one literature review were included within the scoping review. The collective evidence demonstrated that safety culture research is largely based in the USA, within Nursing Homes rather than Residential Home settings. Moreover, the scoping review revealed that empirical evidence has predominantly used quantitative measures, and therefore the deeper levels of culture have not been captured in the evidence base. Conclusions: Safety culture in care homes is a topic that has not been extensively researched. The review highlights a number of key gaps in the evidence base, which future research into safety culture in care home should attempt to address.